Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

How do i solve -(1+7x)-6(-7-x)=36

Sagot :

luana
[tex]-(1+7x)-6(-7-x)=36\\\\-1-7x+42+6x=36\\\\-7x+6x=36+1-42\\\\-x=-5\\\\x=5[/tex]
-(1+7x)-6(-7-x)=36 -- expand brackets
-1-7x+42+6x=36 -- combine like terms
41-x=36 -- add x to both sides and subtract 36 from both sides
5=x

x=5